Analisa Preferensi Kerja Bagi Generasi Z dengan Menggunakan Metode Conjoint Analysis - Muhammad Akbar Rausyan Fikri; Budi Santoso; Agung Wahyu Handaru (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the work preferences of undergraduate management students of Universitas Negeri Jakarta Class of 2020-2021. There are five attributes used to see the importance value of the five attributes, namely salary, career development, work life balance, work location, and work flexibility. Data collection was conducted in Jakarta and Bekasi in April-May 2024. Data collection was carried out using an online questionnaire and respondents were selected using purposive sampling using Slovin. The total respondents in this study were 150 consisting of 73 men and 77 women, all of whom were undergraduate management students in the 2020-2021 batch. This data was processed with exploratory factor analysis and Conjoint Analysis. The result is that one of the attributes that become work preferences for undergraduate management students in the 2020-2021 batch is career development with an importance value of 23.607 and has a utility value of 0.198. importance value of 23.607 and has a utility value of 0.198. Career development that is the highest preference for undergraduate management students in the 2020-2021 generation is a company that offers attractive career opportunities, a company that supports individual career development and actively collects career information.